Internalisasi Nilai-Nilai Religius Pada Siswa Melalui Kegiatan Entrepreneur (Studi Kasus Madrasah Bertaraf Internasional Yayasan Amanatul Ummah Pacet Mojokerto) - Rahmat; Mirdawati (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to describe the forms of entrepreneurial activities, the process of internalizing religious values, and the inhibiting and supporting factors of religious value internalization through entrepreneurial activities at the International Standard Madrasah of Amanatul Ummah Foundation, Pacet Mojokerto. Religious values are not only obtained through obligatory worship but also through non-formal activities such as entrepreneurship, which is an essential soft skill for students in facing the challenges of modern life. This research uses a qualitative method with an in-depth case study approach. The findings show that entrepreneurial activities take two forms: pre-order systems and direct product offerings to consumers. The internalization process of religious values occurs through three stages: value delivery by supervisors, direct student practice, and continuous evaluation. Inhibiting factors include indirect value delivery, lack of individual responsibility, and limited interaction in formal forums. Supporting factors include the enthusiasm of committee members in listening and applying values, mutual reminders among members, and initiatives to conduct periodic evaluations. Entrepreneurial activities have proven effective in instilling discipline, responsibility, and self-confidence in students on a sustainable basis